Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/0969733019836148
|View full text |Cite
|
Sign up to set email alerts
|

Normative nursing ethics: A literature review and tentative recommendations

Abstract: We describe the results and implications of a literature review that identifies the number of normative and empirical articles, respectively, that have appeared in Nursing Ethics in each year from 1994 to 2017. The results of our analysis suggest a powerful trend away from normative scholarship and toward empirical investigation within the field of nursing ethics, both overall and comparatively. We argue that there are several important negative consequences of this trend, and we propose some potential solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
0
6
0
3
Order By: Relevance
“…Seçim özgürlüğü anlamında özerklik, normatif bireyciliğin ilk ve temel bir ifadesidir. 5 Ruhsal sorunlu birey, kendi hastalığını kabul etmese de belirtilerini değerlendirme veya tedavi etmek için özgürlüğüne müdahale etme veya kısıtlama, bireydeki çeşitli nedenlerle azalmış içgörü ve gerçeği değerlendirme yetisi nedeniyle başkalarına ve kendine zarar verme riski olarak tanımlanır. 38 Ancak hasta bireyin isteği olmadan gerçekleştirilen değerlendirme yasal olarak zorunlu da olsa, söz konusu bireyler başka haklar talep etme için mücadele ederler.…”
Section: Ruh Sağliği Ve Psikiyatrik Bakim Uygulamalarinda Normatif Etikunclassified
See 2 more Smart Citations
“…Seçim özgürlüğü anlamında özerklik, normatif bireyciliğin ilk ve temel bir ifadesidir. 5 Ruhsal sorunlu birey, kendi hastalığını kabul etmese de belirtilerini değerlendirme veya tedavi etmek için özgürlüğüne müdahale etme veya kısıtlama, bireydeki çeşitli nedenlerle azalmış içgörü ve gerçeği değerlendirme yetisi nedeniyle başkalarına ve kendine zarar verme riski olarak tanımlanır. 38 Ancak hasta bireyin isteği olmadan gerçekleştirilen değerlendirme yasal olarak zorunlu da olsa, söz konusu bireyler başka haklar talep etme için mücadele ederler.…”
Section: Ruh Sağliği Ve Psikiyatrik Bakim Uygulamalarinda Normatif Etikunclassified
“…Dolayısıyla her 2 sorgulama şekli de kendi başına uygulamayı geliştirmek için yeterli değildir: Ampirik kanıt olmadan normatif araştırma önemsizdir ve normatif analiz olmadan ampirik araştırma tamamlanmamıştır. 5 İlkeler ve değerlerle ilgili ampirik bilgiler karar verme zorunluluğunu ortadan kaldırmadığı gibi tüm bireysel vakalarda belirleyici değildir. Bunlar körü körüne uygulanabilecek matematiksel olarak fizikle ilgili kullanabilecek "doğal yasalar" değildir.…”
Section: Ruh Sağliği Ve Psikiyatrik Bakim Uygulamalarinda Normatif Etikunclassified
See 1 more Smart Citation
“…Applied professional ethics in medicine ( Borry et al, 2005 ; Hedgecoe, 2004 ; Hoffmaster, 2018 ; Mertz and Schildmann, 2018 ), healthcare ( Knight, 2016 ; Vogelstein and Colbert, 2020 ; Wangmo et al, 2018 ), and physical therapy ( Greenfield and Jensen, 2010 ) has increasingly appreciated the importance of the moral experience of practitioners. Focusing on contextual moral experience represents a shift away from the early focus in professional ethics on normative rational philosophical analysis and toward integration of social scientific research ( Borry et al, 2005 ; Hedgecoe, 2004 ; Mertz and Schildmann, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ethical issues are ubiquitous in nursing practice and yet are understudied and undertheorized. Vogelstein and Colbert (2022) identified a dearth of normative ethical inquiry in their review of the literature from 1994 to 2017 and found five times more empirical articles than normative articles. The investigators suggested longer-term approaches to foster increased scholarship in normative ethics, including supporting normative-focused dissertations and promoting coursework and faculty scholars with this focus.…”
mentioning
confidence: 99%